The Influence of Digitization of Information, Promotion, Service Quality, and Company Image on the Decision to Become A Customer Based on Customer Interest as a Moderation Variable - Chasnah Noer Setyani; Dzikrulloh Dzikrulloh (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Customers' interest in sharia products is influenced by several factors. In addition to easy digital access and good promotion, the perception of service quality and the role of the company's image as a trustworthy institution in accordance with sharia principles also has an important role. This study aims to analyze the influence of digitization of information, promotion, service quality, and company image on the decision to become a customer, with customer interest in using products as a moderation variable. The research is positioned in the context of Islamic banking which is accelerating digital transformation to strengthen competitiveness and attract new customers. A quantitative approach is used to test the relationships between variables through structural equation models. The results of the study show that digitalization of technology, sales promotion, service quality, and company image have a significant positive effect on the decision to become a customer, while certain forms of digitization of information and company image have a negative impact on interest in using products. These findings underscore the importance of designing an integrated digital strategy, which focuses not only on the availability of digital channels, but also on the quality of content, consistency of promotional messages, service standards, and institutional reputation management.